Prognostic significance of electrocardiographic findings in angina at rest. Therapeutic implications. Issue 3 (September 1981) - Demoulin, J C; Bertholet, M; Chevigne, M; Legrand, V; Renier, J; Soumagne, D; Soyeur, D; Limet, R; Kulbertus, H
Abstract : Ninety-five patients with angina at rest were observed in the coronary care unit. Eighty-one per cent presented concomitantly or had previously presented some other manifestations of coronary artery disease. These patients were divided into two subgroups. In subgroup 1 (40 patients), episodes of non-exertional angina were associated with a pattern of hyperacute subepicardial injury and, frequently, with ventricular arrhythmias. In subgroup 2 (55 patients), the episodes of angina at rest were attended by horizontal ST depression, isolated T wave inversion, or trivial ST-T changes. Coronary angiographic findings were similar in both subgroups. Symptoms regressed in only 9% of patients in subgroup 1 while they were receiving beta-receptor antagonists, whereas amiodarone alone or amiodarone with nifedipine was successful in 58%. Of these patients, 25% developed a myocardial infarction shortly after admission. In subgroup 2 patients, beta-blockers were successful in 61%. Amiodarone isolated or associated with nifedipine was successful in 55% of the patients in whom it was tried. Only 5% of patients in this subgroup developed a myocardial infarction during their hospital stay. It is concluded that: (1) observation of the electrocardiogram during spontaneous angina in patients with known atherosclerotic coronary heart disease may be of prognostic significance and may influence therapeutic decision. (2) Amiodarone by virtue of its anginal and antiarrhythmic properties may be particularly useful in the treatment of non-exertional angina.